Peran Guru IPS dalam Menanamkan Nilai Karakter Disiplin dan Tanggung Jawab Siswa di SMP Negeri 1 Kunjang Kediri - Ahmad Zaky Muttaqien; Yudi Krisno Wicaksono (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
One of the most important aspects of formal and informal education in educational institutions is character education. Two types of character that should be formed are discipline and responsibility. Possession of discipline and responsibility are highly valued qualities, as character plays an important role in one's daily social interactions. Helping, grouping, and socializing are all included in it. Character development throughout human life as a whole is closely linked to the process of learning and self-formation. Character development can be achieved in the context of family, school, and the environment, which includes communities and groups. The objectives of this study are to (1) describe the teacher's approach in teaching social studies class VIII SMP Negeri 1 Kunjang Kediri that instills the character values of discipline and responsibility. (2) Determine what motivates and what hinders educators to foster the character values of discipline and responsibility in their students through social studies learning in class VIII A of SMP Negeri 1 Kunjang Kediri. (3) To find out the results of social studies learning techniques used to build character values of discipline and responsibility in students of class VIII A SMP Negeri 1 Kunjang Kediri. A descriptive qualitative approach was used in this study. In collecting data, the methods used were observation, interviews, and documentation. The Miles and Huberman approach was used in the design of this research, which used descriptive analysis techniques through three stages: data reduction, data display, and conclusion drawing. Triangulation of data sources was used in assessing the validity of the data. The teachers and students of SMP Negeri 1 Kunjang Kediri became the research subjects. Based on the data analysis, the following conclusions were obtained: 1) Motivation and exemplary teachers, active involvement of students in learning, self-habituation, and sanctioning violations are strategies used by social studies teachers at SMP Negeri 1 Kunjang Kediri, 2) Strong motivation, family support, school regulations, and the environment are the driving factors faced by social studies teachers at SMP Negeri 1 Kunjang Kediri in instilling the character values of discipline and responsibility to students. Meanwhile, the unsupportive atmosphere and students' lack of willingness to learn make them less effective learners are the inhibiting factors. In this case, the teacher's duties have been carried out in accordance with their responsibilities as educators, motivators, mentors, and assessors. 3) The results of the social studies teacher's strategy in the implementation of cultivating the character of discipline and responsibility for students in grade VIII through motivating activities, students become enthusiastic in discipline and responsibility for the mandate carried out, namely as students. Through exemplary, students have successfully applied and instilled forms of discipline and responsibility in terms of dress, time, and duties through their active participation in classroom learning. This is indicated by students' active participation in discussions, students' activeness in completing and collecting assignments given by the teacher, students' enthusiasm for learning that is always high, self-habituation that has been applied by social studies teachers, the ability of social studies teachers to train students to be more disciplined and responsible in terms of worship, students' habits to help others and parents, and the appearance of disciplined and responsible students, by making efforts to impose sanctions on students who commit violations so that they do not repeat them again and encourage them to be more aware of their obligations as students.